Community perceptions of tourism development in rural area of Tsatsane Lesotho - Phasumane, Palesa Edith; Onojaefe, Darlington; Stuma, Phelokazi; Ukpere, Wilfred; Adekanmbi, Foluso (Annals of Spiru Haret University. Economic Series, 2023)
This paper investigated community perceptions of tourism development and identified the relationship between tourism development projects and business opportunities in Tsatsane community, Lesotho. This investigation was done using a qualitative research method to understand the relationship between respondents’ perceptions of tourism development projects and associated business opportunities. Using purposive random sampling techniques, 30 respondents comprising of 19 community members, 2 community leaders, and 9 stakeholders were chosen and interrogated. After the choice, qualitative data were gathered using an open-ended semi-structured interview guide. Thematic analysis was used to organize the themes that emerged from the responses after they were transcribed. Using Atlas Ti.8, similar themes were gathered and transferred. The study found a significant relationship between tourism development projects and recurrent themes like new knowledge of tourism-related business opportunities, job creation, increase in trade, and education. Although few respondents have different opinions